Penerapan Sistem Kontrol Optimal Pada Kursi Roda - Tommy P.J. Sibuea; Vecky C. Poekoel; Feisy D. Kambey (Universitas Sam Ratulangi, 2018)
Abstract - For physically handicapped, wheelchairs are one of the main tools used for doing their activities. In addition to physical disabilities, wheelchairs are also commonly used in hospitals to carry patients, existing wheelchairs are still being moved manually and slightly tiresome to its users. Auto wheelchairs are tools used for people who are having trouble walking well due to illness, injury, or disability. These wheelchairs can be driven or use an automatic motor depending on the situation. In this research, Wheelchairs are designed to be stable at fixed speeds, both on flat and uphill tracks, using PID controllers. Based on the design in the test, it is found that the constant constant value of the constant flat path is P = 0.35, I = 0.5, D = 0.1. And on the uphill trajectory using stable PID value is P = 9, I = 0.009, D = 4.05. Testing was performed at the Control and Road Laboratory with 10 Meters distance. Smart wheelchairs can navigate semiautonomous by using joystick movement controls, which ensure users can use this wheelchair easily. The use of Arduino ATmega 2560 as the center of the controller of the wheelchair system can be modified into several types of speed for example (slow, fast, and very fast) according to the adjustment of the motor's ability and battery, because the faster the PG45 motor rotates, the higher the voltage and current requiredKeywords — Joystick; Velocity; Wheel chair; PID Abstrak - Bagi penyandang cacat fisik, kursi roda merupakan salah satu alat bantu utama yang banyak digunakan untuk melakukan aktifitasnya. Selain untuk penyandang cacat fisik, kursi roda juga biasanya digunakan di rumah sakit untuk membawa pasien. Kursi roda otomatis dapat digunakan pada lintasan datar dan menanjak pada sudut 1.90 – 5.30 dengan kontrol dari joystick. Sesuai perancangan dalam pengujian yang telah dilakukan, maka didapatkan nilai konstanta PID terbaik untuk lintasan datar yang stabil yaitu P = 0.35, I = 0.5, D = 0.1. Pada lintasan menanjak menggunakan nilai PID yang stabil yaitu P = 9, I = 0.009, D = 4.05. Kursi roda cerdas dapat bernavigasi secara semiautonomous dengan menggunakan control gerakan joystick, yang memastikan pengguna dapat menggunakan kursi roda ini dengan mudah. Penggunaan arduino ATmega 2560 sebagai pusat pengontrol dari sistem kursi roda ini dapat dimodifikasi menjadi beberapa type kecepatan misalnya (slow, fast, and very fast) sesuai penyesuaian dari kemampuan motor beserta aki nya, karena semakin cepat motor PG45 berputar maka semakin tinggi juga tegangan dan arus yang di perlukan. Pengujian dilakukan Di Laboratorium kendali, Lintasan menanjak 1.90 – 5.30 dan Jalan aspal dengan jarak 10 Meter.Kata kunci — Joystic; Kecepatan; Kursi Roda; PID